SURVIVORSHIP NAVIGATION OUTCOME MEASURES: A report from the ACS Patient Navigation Working Group on Survivorship Navigation - Pratt-Chapman, Mandi (2011)
Survivorship navigation is a relatively new concept in the field of patient navigation, but an important one. This paper highlights the essential functions of the survivorship navigator and defines core outcomes and measures for navigation in the survivorship period. Barriers to access to care experienced by patients during active cancer treatment can continue into the post-treatment period, affecting quality follow-up care for survivors. These barriers to care can be particularly acute for non-English speakers, immigrants, the uninsured, the underinsured and other vulnerable populations. The survivorship navigator can help reduce barriers and facilitate access to survivorship care and services through communication and information exchange for patients. Survivorship navigation may improve appropriate health care utilization through education and care coordination, potentially improving health outcomes and quality of life of survivors while reducing cost to the health care system. Survivorship navigators can also educate survivors on how to improve their overall wellness, thereby directly impacting the health of a growing population of cancer survivors.